Photon diagnostics for the seeding experiment at FLASH - Curbis, F. ; 0000-0002-7703-9232; Azima, A.; Boedewadt, J.; Delsim-Hashemi, H.; Drescher, M.; Maltezopoulos, T.; Miltchev, V.; Mittenzwey, M.; Rossbach, J.; Tarkeshian, R.; Wieland, M.; Duesterer, S.; et al. (31st International Free Electron Laser Conference, FEL 2009, Liverpool, United Kingdom, 2009-08-23 - 2009-08-28, 2009)
Starting from next year the technical feasibility of a direct seeding scheme at 30 and 13 nm will be studied at the Free-electron LASer in Hamburg (FLASH). During a major shutdown the SASE-FEL facility will be upgraded and it is planned to install in addition a high-harmonic generation (HHG) seed laser, a new chain of 10 m variable gap un-dulators and a dedicated commissioning beamline for photon diagnostics and pilot time-resolved pump-probe experiments. Besides demonstrating successful seeding at short wavelength, the project aims for time resolution in the 10 fs range to study ultrafast processes by combining the naturally synchronized FEL and optical seed laser pulses. After the extraction of the radiation in a magnetic chicane, a short branch will accommodate intensity and beam monitors and a high-resolution spectrometer. The intensity monitor detects scattered photons from a gold mesh on a shot-to-shot basis using micro-channel plates (MCP) and XUV diodes. It is designed to detect photons several orders of magnitude apart in flux, i.e. spanning the wide range from spontaneous emission up to the seeded FEL radiation at gigawatt power level. Simulations of this device are presented as well as calibration measurements carried out at FLASH.